Resume Literatur Kajian Pustaka Jurnal Terkait: Pengaruh Risk Assessment dan Safety Culture terhadap Peningkatan Kinerja K3 pada Industri Pulp dan Kertas - Anto Maryadi; Nurulia Hidayah (Jurnal Kesehatan Amanah, 2025)
Paper-based products play a vital role in various aspects of modern life, ranging from educational and office needs to industrial and e-commerce applications. This study aims to analyze the impact of implementing risk assessment and safety culture on improving Occupational Health and Safety (OHS) performance in companies through a systematic literature review method. The research process involved identifying five relevant journal articles from various academic databases using strict inclusion and exclusion criteria. Data and findings from the selected literature were then collected, analyzed, and synthesized to gain a comprehensive understanding of the relationship between risk assessment, safety culture, and OHS performance. The results indicate that comprehensive risk assessment implementation and strong safety culture development significantly contribute to improved OHS performance. These findings are particularly relevant for the pulp and paper mills industry, which faces high workplace risks. The study recommends that companies adopt a systematic approach to risk manajement and consistently develop safety culture to create a safer work environment and support smooth business operations.